Peran Sektor Pertanian terhadap Perekonomian Kabupaten Hulu Sungai Utara - Azwar Saihani; Purna Kusumayana; Laila Mayang Sari (Rawa Sains: Jurnal Sains STIPER Amuntai, 2020)
This study aims to determine the contribution, position, growth, and basis and non basis of each agricultural subsector to the GRDP in the economy of Hulu Sungai Utara Regency from 2013-2017. The data used is secondary data originating from the Central Bureau of Statistics and related government agencies. The analytical method used is contribution analysis, typology of class, shift share and LQ. The results showed that of the five agricultural sub-sectors in North Hulu Sungai Regency the highest contribution to the agricultural sector was the food crop subsector in the past five years at 61.07%. The position of the five agricultural sub-sectors is in the third place, which means that the five subsectors are potential or can still develop. The growth of each agricultural sub-sector in the economy of Hulu Sungai Utara Regency varies from the proportional growth of the food, livestock and fisheries sub-sectors to rapid growth while the horticulture and plantation subsectors experienced slow growth. The five agricultural sub-sectors are not competitive or lack competitiveness with other regions in South Kalimantan Province. The subsector which is the subsector of the base is the food, livestock and fisheries subsector while the horticulture and plantation subsector is the non-base sub-sector in North Hulu Sungai Regency.